(untitled) (Revista de Ciência Veterinária e Saúde Pública, 2020)
This paper objective has been to evaluate the effectiveness of hemoacupuncture as a complementary treatment of thrombocytopenia related to canine ehrlichiosis. Seventeen (17) dogs were used, males and females, with platelet count below 200.000/Î¼.L. The animals were distributed into two groups: Control (C, n =10) – animals which received conventional treatment with Doxycycline hydrochloride (10 mg/kg, BID); and Treatment (T, n =7) – animals which received conventional therapy associated with hemoacupuncture in the acupoints BL17, GB39, SP10 and GV14. The treatment was accomplished in four weeks, accounting with hemoacupuncture sessions weekly. Every seven days, a new complete blood count (CBC) was prepared in order to evaluate the effect of the therapy. The data assessment did not demonstrate differences between treatments in any appraised moment. In these conditions, the use of hemoacupuncture did not present an incremental in the treatment of dogs’ thrombocytopenia